Smart RFID system for oil palm bio-laboratory - Aziz N.H.A.; Alias A.J.; Hashim A.T.; Mustafa R.; Anuar K.; Ahmad S.; Muhamad W.N.W. (2023)
The tissue culture laboratory provides the oil palm industry with innovations for the production of improved planting materials and information on the molecular biology of tissue culture processes. Research has shown that factors such as temperature, humidity, liquid, phase and gas compositions, are critical in producing quality clonal materials using tissue culture process. Therefore, it is necessary to provide good physical and chemical conditions for production of quality products. Consequently, sensors are required to monitor and record the data in growth room. All sensors will monitor critical parameters that focus on temperature, humidity, oxygen, carbon dioxide, ethylene and also an optical sensor for liquid phase and composition that will be linked to the database and analysis software for storing and analyzing the monitored data. The integrated sensors are low cost because it used local products and low power consumption and fabricated to suit the biological laboratory environment. The purpose of these integrated biotechnology sensors system is to serve as an interface among user, as the disturbance analysis program and an expert system in identifying the disturbance. The system would monitor via a smart RFID telemetry system and provide automatically email or short message (SMS) notifications upon identification of a disturbance module. Radio-frequency identification (RFID) is an automatic wireless identification method using radio waves, relying on storing and remotely retrieving data from integrated sensors using devices called RFID tags or transponders. Some tags can be read from several meters away and beyond the line of sight of the reader which make easier for data transportation. For the best communication path, active RFID tags will be equipped with autonomous networking; which greatly improves the utility of the device. Eventually, this smart RFID technology system could improve the efficiency of inventory tracking and management for oil palm tissue culture growth. 2008 IEEE.